Winter legume cover crop with adequate nitrogen fertilization enhance dryland maize yield and water-use efficiency - Jinfa Chen; Upendra M. Sainju; Rui Liu; Guangye Tan; Mengmeng Wen; Jie Zhao; Jinlin Pu; Jiangru Feng; Jun Wang (Agricultural Water Management)
Winter cover crops can provide multiple ecosystem services but can reduce succeeding maize (Zea mays L.) yield and water-use efficiency (WUE) by depleting soil water compared with no cover crop in arid and semi-arid regions. We examined the impacts of winter cover crops (lentil [Lens culinaris L.], oat [Avena sativa L.], lentil/oat mixture, and no cover crop) and nitrogen fertilization rates (0, 165, and 220 kg N ha1) to succeeding maize on soil water storage at planting (SWP) and harvest (SWH) at the 0–2 m depth, evapotranspiration (ET), maize yield, and water use efficiency (WUE) from 2017 to 2022 in the Loess Plateau of China. We measured cover crop biomass and maize yield at harvest, SWP and SWH using a soil probe, and ET and WUE based on growing season precipitation and water use. Cover crop biomass yield was 59–134 % greater for oat with 220 kg N ha−1 than lentil with other N fertilization rates. The SWP was 5–22 % greater for no cover crop with 0 kg N ha−1 than other cover crops with N fertilization rates. The SWH and ET varied with cover crops, N fertilization rates, and years. Maize yield and WUE were 12–42 % greater for lentil with 220 kg N ha−1 than oat and no cover crop with other N fertilization rates. Although cover crops depleted soil water at maize planting, lentil cover crop with 220 kg N ha−1 can enhance maize yield and WUE compared with other cover crops and N fertilization rates in the Loess Plateau of China.